2018
DOI: 10.3389/fmicb.2018.00552
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Indirect Effects of Penguin Feces on Microbiomes in Antarctic Ornithogenic Soils

Abstract: Expansion of penguin activity in maritime Antarctica, under ice thaw, increases the chances of penguin feces affecting soil microbiomes. The detail of such effects begins to be revealed. By comparing soil geochemistry and microbiome composition inside (one site) and outside (three sites) of the rookery, we found significant effects of penguin feces on both. First, penguin feces change soil geochemistry, causing increased moisture content (MC) of ornithogenic soils and nutrients C, N, P, and Si in the rookery c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 56 publications
2
17
0
Order By: Relevance
“…The hydrophobicity of these soils could benefit to the deep-rooted camel thorn trees in that competition from subcanopy vegetation is excluded. Furthermore, continuous deposition of feces by the weavers can lead to a change in soil microbial communities as has been previously shown to happen with penguin activity in maritime Antarctica (Guo et al, 2018). As such, changes in microbial communities can also potentially affect the establishment of plants (Hartman & Tringe, 2019;Raaijmakers, Paulitz, Steinberg, Alabouvette, & Moënne-Loccoz, 2009) and lead to the observed barren areas directly beneath the nests (Guyonnet et al, 2017;Pochana & Keller, 1999).…”
Section: F I G U R Ementioning
confidence: 87%
“…The hydrophobicity of these soils could benefit to the deep-rooted camel thorn trees in that competition from subcanopy vegetation is excluded. Furthermore, continuous deposition of feces by the weavers can lead to a change in soil microbial communities as has been previously shown to happen with penguin activity in maritime Antarctica (Guo et al, 2018). As such, changes in microbial communities can also potentially affect the establishment of plants (Hartman & Tringe, 2019;Raaijmakers, Paulitz, Steinberg, Alabouvette, & Moënne-Loccoz, 2009) and lead to the observed barren areas directly beneath the nests (Guyonnet et al, 2017;Pochana & Keller, 1999).…”
Section: F I G U R Ementioning
confidence: 87%
“…It will be useful in revealing the genetic polymorphism in general and aiding identifying the causative human pathogens or environmental disease vectors. WITOD is available at https://github.com/johncava/WITOD Background In microbiome research, current analysis of 16S rRNA gene amplicons is generally focused on the abundance of operational taxonomical units (OTUs) and the taxa which they belong to (e.g., Guo et al 2018). However, the biodiversity within taxa has been rarely studied, although it is important to both general microbiome compositional structure dissection and accurate diagnosis of human pathogens (Faith et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The link between penguins and geochemical altercations of local soil was first expressed in Liguang et al (2004), who used a sulfur, phosphorous, calcium, copper, zinc, selenium, strontium, barium, and fluorine chemical array to infer historical penguin density. Like Guo et al (2018), the researchers demonstrated that nitrogen and phosphorus were strongly correlated with penguin droppings. However, toxification of the soil can occur in particularly dense colonies, precluding floral growth through both trampling and metal prevalence.…”
Section: Ridgwell and Kohfeld 2005)mentioning
confidence: 94%